MENINGKATKAN ANTUSIASME BELAJAR DAN PEMAHAMAN KONSEP MATERI IPAS KESEHATAN LINGKUNGAN DI SD SUNGGUMINASA II MELALUI PENERAPAN GAME EDUKATIF WORDWALL DALAM MODEL PEMBELAJARAN BERBASIS MASALAH - Hikmah Sastia Dewi; Ainun Mutmainna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to enhance the learning enthusiasm of sixth-grade students regarding the Science and Social Studies (IPAS) material related to environmental health through the implementation of the educational game WordWall within a problem-based learning model. The type of research employed is classroom action research (CAR) with a collaborative design involving two cycles. Each cycle consists of stages of planning, implementation, observation, and reflection. In the first cycle, students were introduced to an educational game designed to facilitate their understanding of environmental health concepts. Following the activities, observations were made regarding student engagement and responses. Based on the reflection results, actions were refined and improved in the second cycle by adding variations of games and group discussion methods. The research findings indicate a significant increase in students' learning enthusiasm. In the first cycle, the average engagement score was recorded at 65%, which rose to 85% in the second cycle. Additionally, students' understanding of the material also improved, with the average final test score increasing from 70 in the first cycle to 85 in the second cycle. These findings suggest that the implementation of educational games in problem-based learning is effective in enhancing students' interest and understanding of IPAS material. This study recommends the use of other interactive methods to support classroom learning